PRELIMINARY STUDY OF SPECIES COMPOSITION AND DISTRIBUTION OF BEETLES (INSECTA: COLEOPTERA) IN DU GIA COMMUNE, DU GIA NATIONAL PARK - DONG VAN KARST PLATEAU, TUYEN QUANG PROVINCE - Minh Hong, Bui; Phuong Thao, Vu; Thi Le Quyen, Ca; Thi Tuyet, Vu; Thi Thu Huong, Nguyen (HNUE Journal of Science: Journal of Natural Sciences, 2025)
This study investigated the species composition and distribution of beetles across three habitats in Du Gia commune, located within Du Gia National Park - Dong Van Karst Plateau, Tuyen Quang Province. The study employed a direct survey of beetles across three habitats, conducted over three sampling periods. A total of 39 beetle species, belonging to 10 families and 33 genera, were recorded. The family Coccinellidae contained the highest number of taxa, with 13 species (33.33%) and 10 genera (30.30%). Three families, Phalacridae, Ptinidae, and Scarabaeidae, had the lowest number, each with one species (2.56%) and one genus (3.03%). The distribution of beetle species varied among habitats. The natural forest habitat supported the highest diversity, with 38 species (97.45%) recorded; followed by the grassland and shrub habitat on the mountainside with 34 species (87.18%); and the agricultural land and fruit tree habitat with 24 species (61.52%). The composition of beetle species also varied across survey phases. Phase 1 (October 2024) yielded the highest species richness, with 39 species recorded (100%); Phase 2 (January 2025) with 21 species (53.85%); and Phase 3 (March 2025) with 35 species (89.74%).